Sustained uptake of LPG as cleaner cooking fuel in rural India: Role of affordability, accessibility, and awareness. (December 2016) - Kumar, Praveen; Kaushalendra Rao, R.; Reddy, N. Hemalatha
Highlights: Energy-society relationship in poor communities is intricate. Sustained adoption of LPG is a function of affordability, accessibility, and awareness of poor communities. Abstract: India is witnessing gradual increase in domestic consumption of LPG for past few decades. As a part of journey towards low carbon economy, a concerted push is been given towards promotion and adoption of cleaner cooking technologies especially LPG at household level in rural areas where bulk of population resides. There are sustained efforts being made by government to overhaul their subsidy systems, introduce pro-poor financial schemes, and bolster infrastructure so as to increase adoption and use of LPG in the rural landscape. Despite such initiatives, demand side issues of adoption, sustained and exclusive use of LPG by these communities remain. We argue in the paper that uptake and sustained use of LPG is a function of economic and social determinants, which have not been systematically studied so far. Energy-society relationship is intricate. Vulnerability of energy poor population exacerbates the intricacies of this relationship. Evidence base on strategies fostering uptake and sustained use of LPG among energy poor communities is weak and anecdotal. Unless we explore the economic and social determinants of adoption and sustained use of LPG, larger policy level initiatives on pro-poor LPG dissemination will not render adequate success to address energy poverty. Evidence suggests that adoption and sustained use of LPG is impacted by affordability, accessibility, and awareness (3As) issues. Systematic research is needed to undertake a concurrent analysis of the 3As and their corresponding impact on both adoption and sustained use of LPG in rural households.